PENGAMATA PENEBANGAN DAN PENGANGKUTAN SAGU DI DESA TANJUNG KECAMATAN TEBING TINGGI PROPSI RIAU - Wesman Endom (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
ln indonesia Sago (Metroxylon sp) is one of the natural resources which is potenlally great enaugh for developing national income. The areas distribute over many places particularly in Irian. Jaya, Maluku, some parts of Sulawesi, Kalimantan and Sumatera, covering ± 6 00 000 ha.In Sumatera, sago grow in swampy area like South Sumatera, Jambi, Riau and Aceh. ln Riau the most famous producer sago area is Sab Districl of Tebing Tinggi of District Bengkalis . According to the last report of 1989, the total sago area in Sub District of Tebing tinggi is± 15 915 ha, and has producted sago of 156 500 ton.This paper discussing same aspects of technical harvesting of sago. which has preliminary observed in an area of the farmer as one of the sharing sago cooperation of Harmonis, that localed in Desa Tanjung. Sub District of Tebing Tinggi. Those aspects were felling, toping and branching and tranportalion with and addition of sago proccesing. The resul: showed that felling topping and branching and sago tranportation are carried out by group of felling operation wkich is consist of 6-8 men/group. the salary system is done by contract.The sagos are felled before flowering and each trees was cut wilh diameter ranged.from 49-64 cm and need ± 16,1 minutes/tree.the log then cutted after lopping and branching into 8-11 pieces depend on the tog length 1, 05-1 ,25 m/pieces. This pieces are called tual. Each tual then hauled using manual system as well as